Reducing Inequality through Parental Support: Building Social Resilience in Indonesia’s Indigenous Religious Communities - Novianti Wiwik; Noegroho Agoeng; Saputra Diki; Bunga Maharani Annisa; Lotulung Leviane J.H.; Pinky Syalomita Kimberly; Desmiwati Desmiwati (E3S Web of Conferences)
In Indonesia, indigenous religious believers have faced stigma for decades, primarily due to past restrictions that prevented them from including their religious identity on official documents. This exclusion has led to bullying, discrimination, and feelings of inferiority among these communities. Many believers perceive their religious identity as the cause of the discrimination they face, which is reinforced through negative social interactions. This study explores the role of parents in building social resilience among indigenous religious believers, focusing on how parent-child communication fosters this resilience. Using a phenomenological approach, the research gathered data through interviews and observations with 15 participants from various indigenous religious communities in Indonesia. The findings reveal that parents are crucial in transmitting indigenous religious practices and values through both verbal and non-verbal communication. By fostering pride in their faith, parents help their children build resilience, allowing them to maintain their religious identity in the face of societal challenges and negative external influences. The study has broader implications for policies promoting social inclusion, reducing inequalities, and strengthening family and community roles in supporting marginalized groups. It contributes to Sustainable Development Goal (SDG) 10, advocating for structural changes that promote diversity and social equality.